A sulfur vacancy rich CdS based composite photocatalyst with g-C3N4 as a matrix derived from a Cd–S cluster assembled supramolecular network for H2 production and VOC removal. Issue 12 (26th February 2018) - Wang, Yaqin; Xu, Xinxin; Lu, Wei; Huo, Yuqiu; Bian, Lijun
Abstract : A sulfur vacancy rich CdS based composite photocatalyst with g-C3 N4 as a matrix has been synthesized from a tetranuclear Cd–S cluster assembled supramolecular network. Abstract : By calcination, a sulfur vacancy rich CdS based composite photocatalyst with graphitic carbon nitride (g-C3 N4 ) as a matrix has been synthesized successfully from a tetranuclear Cd–S cluster assembled supramolecular network. In this photocatalyst (CdS@g-C 3 N 4 ), CdS nanoparticles with a size of about 5 to 8 nm disperse homogenously in the g-C3 N4 matrix. During calcination, some coordinated nitrogen atoms dope in the lattice of CdS and replace sulfur atoms, which generates a large number of sulfur vacancies. Under visible light irradiation, CdS@g-C 3 N 4 exhibits excellent H2 production activity with a rate achieving as high as 19.88 mmol g −1 h −1 in the absence of a Pt cocatalyst. Its H2 production ability remains stable for 30 h, which does not decay. Besides H2 production, CdS@g-C 3 N 4 also shows excellent photocatalytic activity for Volatile Organic Compound (VOC) degradation. For a photocatalyst, chemical content plays an important role in its performance. Here, the influence of sulfur vacancies on H2 production and VOC degradation is discussed in detail. We expect that the sulfur vacancy rich CdS@g-C 3 N 4 can act as an efficient material for H2 production and indoor air purification.